Feasibility and Acceptability of Wearable Sensor Placement for Measuring Screen Time of Children. Issue 4 (14th October 2022) - Willis, Erik A.; Hales, Derek; Smith, Falon T.; Burney, Regan; El-Zaatari, Helal M.; Rzepka, Michelle C.; Amft, Oliver; Barr, Rachel; Evenson, Kelly R.; Kosorok, Michael R.; Ward, Dianne S.
ABSTRACT: Introduction/Purpose: Wearables that include a color light sensor are a promising measure of electronic screen use in adults. However, to extend this approach to children, we need to understand feasibility of wear placement. The purpose of this study was to examine parent perceptions of children's acceptability of different sensor placements and feasibility of free-living 3- to 7-d wear protocols. Methods: This study was conducted in three phases. In phase 1, caregivers ( n = 161) of 3- to 8-yr-old children completed an online survey to rate aspects of fitting and likelihood of wear for seven methods (headband, eyeglasses, skin adhesive patch, shirt clip/badge, mask, necklace, and vest). In phase 2, children ( n = 31) were recruited to wear one of the top five prototypes for 3 d ( n = 6 per method). In phase 3, children ( n = 23) were recruited to wear one of the top three prototypes from phase 2 ( n = 8 per method) for 7 d. In phases 2 and 3, parents completed wear logs and surveys about their experiences. Parents scored each wearable on three domains (ease of use, likelihood of wear, and child enjoyment). Scores were averaged to compute an everyday "usability" score (0, worst, to 200, best). Results: Phase 1 results suggested that the headband, eyeglasses, patch, clip/badge, and vest had the best potential for long-term wear. In phase 2, time spent wearing prototypes and usability scores were highest for the eyeglasses (10.4 h·d −1 ; score, 155.4), clip/badge (9.8 h·d −1 ; score, 145.8), and vest (7.1 h·d −1 ; score, 141.7). In phase 3, wearing time and usability scores were higher for the clip/badge (9.4 h·d −1 ; score, 169.6) and eyeglasses (6.5 h·d −1 ; score, 145.3) compared with the vest (4.8 h·d −1 ; score, 112.5). Conclusions: Results indicate that wearable sensors clipped to a child's shirt or embedded into eyeglasses are feasible and acceptable wear methods in free-living settings. The next step is to assess the quality, validity, and reliability of data captured using these wear methods.